Obosnovanie effektivnosti metodiki soveršenstvovanija gruppovych takticeskich dejstvij chokkeistov 10-11 let - Timchenko, T. V.; Khammatov, B. M.; Yulamanova, G. M.; Danilov, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article proved efficiency of the developed technique designed to improve the group tactical actions of hockey players, aged 10-11 years old, applying inter-group analysis of the indicators of the level of the group tactics and leading properties of attention of the players at the age of 10-11 years. The technique includes the tactical tasks, mainly aimed at improving the most effective group tactical actions in the competitive games of the qualified hockey players, and special tasks aimed at forming the leading properties of attention.